Ancient Manuscripts of Kerinci: Aksara Incung in the Course of History - Gandi, Indra Muhammad (Contemporary Society and Politics Journal, 2024)
Each region has numerous historical sites developed as a form of cultural heritage preservation, including Indonesia, which is home to various ancient manuscripts. One of the most significant ancient manuscripts is the Kerinci Manuscript, written in the Incung script. The Incung script was used by the Kerinci people to document spells, customary laws, and other important records. However, this script has largely been forgotten by the younger generation of Kerinci. This study aims to explore the history, functions, and development of the Kerinci Incung script. The research employs a qualitative historical method through literature review. The findings reveal that the Incung script has a long history and diverse functions, ranging from serving as a medium for writing legal codes and historical records to oral literature. The script was inscribed on various media such as buffalo horns, bamboo, tree bark, and paper. Although it is less known today, efforts to preserve it are ongoing, including through education and cultural events. This study underscores the importance of the Incung script as a cultural heritage that needs to be preserved and developed to enrich the cultural identity of the Kerinci community.